Análise de políticas públicas: Uma revisão da literatura sobre o papel dos subsistemas, comunidades e redes - Capella, Ana Cláudia Niedhardt [UNESP]; Brasil, Felipe Gonçalves (My University, 2015)
From theoretical approaches to its incorporation in recent models of policies analysis, the subsystems have gained a prominent role in the international literature of public policies. The objective of this paper is to present the construction of the concepts of subsystems, policy communities and policy networks and check how the most recent theoretical models use these subunits as the locus of interaction between different actors, institutions and ideas to analyze the policy process.
Keywords: Policy analysis; Policy subsystems; Public policy; Subsystems